Catastrophic Health Expenditures And Impoverishment In Kenya - Kimani, Diana N.; Mugo, Mercy G.; Kioko, Urbanus M. (European Scientific Journal, ESJ, 2016)
Background: Out-of-pocket health expenditures leave households exposed to the risk of financial catastrophe and poverty whenever they entail significant dissaving or the sale of key household assets. Even relatively small expenditures on health can be financially disastrous for poor households and similarly, large health care expenditures can lead to financial catastrophe and bankruptcy for rich households. Objective: There is increasing evidence that out-of-pocket expenditures act as a financial barrier to accessing health care, and are a source of catastrophic expenditures and impoverishment. This paper estimates the burden of out-of-pocket payments in Kenya; the incidence and intensity of catastrophic health care expenditure and impoverishment in Kenya. Methods: Using Kenya Household Health Expenditures and Utilization Survey data of 2007, the study uses both descriptive and econometric analysis to investigate the incidence and intensity of catastrophic health expenditures and impoverishment as well as the determinants of catastrophic health expenditures. To estimate the incidence and intensity of catastrophic expenditures and impoverishment, the study used both Wagstaff and van Doorslaer, (2002) and Xu et al. (2005) and applied various thresholds to demonstrate the sensitivity of catastrophic measures. For determinants of catastrophic health expenditures, a logit model was employed. Findings: Among those who utilized health care, 11.7 percent experienced catastrophic expenditures and 4 percent were impoverished by health care payments. In addition, approximately 2.5 million individuals were pushed into poverty as a result of paying for health care. The poor experienced the highest incidence of catastrophic expenditures. Conclusion: The paper recommends that the government should establish avenues for reducing the burden of out-of-pocket expenditures borne by households. This could be through a legal requirement for everyone to belong to a health insurance and targeting the poor, the elderly and chronically ill through the devolved system of the government and devolved funds.